Imperial brotherhood : gender and the making of Cold War foreign policy - Dean, Robert D., 1956- (Culture, politics, and the Cold War., 2001)
An analysis of how culture, class and gender shaped American foreign policy during the Cold War. The author examines the institutions that shaped the members of the US foreign policy establishment, including all-male prep schools and Ivy-League universities.